Who can claim innovation and benefit from it? Gender and expectancy violations in reward-based crowdfunding - Benedikt David Christian Seigner; Hana Milanov; Aaron F. McKenny (Strategic Entrepreneurship Journal, 2022)
Although reward-based crowdfunding is lauded for its promise to democratize funding for innovation, claiming innovation in campaign texts has an ambiguous link to crowdfunding performance. We draw from Expectancy Violations Theory (EVT) and, in a field study of 2,185 Kickstarter campaigns, find that innovation claims yield better fundraising performance for women than men, particularly in male-stereotyped categories. An experiment did not identify the expected indirect effects of innovation claims on crowdfunding performance through ability trustworthiness. However, it revealed that women are perceived as more able when launching campaigns in male-stereotyped categories, suggesting that EVT and ability perceptions may still play an important but unhypothesized role. We extend research on the role of gender in crowdfunding and strategic entrepreneurship and make several suggestions for future research. Managerial Summary The value of making innovation claims in reward-based crowdfunding is ambiguous, creating an unclear picture of how entrepreneurs should present new products on these platforms. In a field study of 2,185 Kickstarter campaigns, we show that female entrepreneurs benefit more from making innovation claims than their male peers, especially in male-dominated categories. While we suggested that these effects occur due to differences in backers' perceptions of the entrepreneur's ability, this mechanism was not supported in an experiment. However, we found that women are perceived as more able when launching crowdfunding campaigns in male-dominated industry categories. Taken together, our research suggests that in reward-based crowdfunding, women might benefit from violating gender expectations when backers view these violations as either positive or ambiguous.
Keywords: 650; crowdfunding; expectancy violations theory; innovation; mixed methods; women's entrepreneurship